Determinants of Corporate Investments in Innovativeness – Evidence from Central and Eastern European Countries - Barbara GRABINSKA; Konrad GRABINSKI (Communications of International Proceedings, 2020)
The aim of the paper is to investigate the determinants of investment in innovativeness in the case of companies from the Central and Eastern European Countries (CEECs). To adress the problem of underreporting of R&D expenditure which seemes to be especially evident in emerging economies, we develop a proxy for the intensity investments in innovativeness. We hypothesize that financial leverage is negative and profitability and effectiveness of public support system are positive determinants of R&D. As a proxy for the effectiveness of the public policy supporting investments in innovativeness, we use a composite metric developed by OECD – implied tax subsidy rate on R&D expenditures. Our sample consists of firm-year observations from the period 2010-2018 of large and very large firms from: the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia. These countries besides all being the new members of the European Union from 2004,  represent a similar level of economic and institutional development, share the communist heritage and a common set of cultural values. Using panel regression with robust standard errors, we provide empirical evidence supporting our hypotheses. The results of the study may be of interest to policymakers and scholars from emerging markets.
Keywords: R&D determinants; innovation policy; R&D tax subsidies; R&D intensity